2015
DOI: 10.1002/bies.201500094
|View full text |Cite
|
Sign up to set email alerts
|

Simulation of enamel wear for reconstruction of diet and feeding behavior in fossil animals: A micromechanics approach

Abstract: The deformation and wear events that underlie microwear and macrowear signals commonly used for dietary reconstruction in fossil animals can be replicated and quantified by controlled laboratory tests on extracted tooth specimens in conjunction with fundamental micromechanics analysis. Key variables governing wear relations include angularity, stiffness (modulus), and size of the contacting particle, along with material properties of enamel. Both axial and sliding contacts can result in the removal of tooth en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 101 publications
0
30
0
Order By: Relevance
“…In addition, an experimental study on the behavior of enamel under various biomechanic constraints suggests that thick enamel could be an adaptive trait to deal with foods either hard or tough, laden with particulates, potentially including both grit and phytoliths 81 . A recent study observed a low frequency of enamel chipping in P. robustus, concluding that it was not adapted to eating hard foods 82 , but rather tough vegetation.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, an experimental study on the behavior of enamel under various biomechanic constraints suggests that thick enamel could be an adaptive trait to deal with foods either hard or tough, laden with particulates, potentially including both grit and phytoliths 81 . A recent study observed a low frequency of enamel chipping in P. robustus, concluding that it was not adapted to eating hard foods 82 , but rather tough vegetation.…”
Section: Methodsmentioning
confidence: 99%
“…By contrast, the overall larger M 1 roots with similar-proportioned buccal and palatal roots in P. robustus (and P. boisei ) seem to imply more vertical (axial) loading at, perhaps, higher bite forces [61,63,64]. When viewed within the broader context of the orofacial skeleton, these results provide more nuanced insights into the dietary adaptations of early Pleistocene hominins.…”
Section: Discussionmentioning
confidence: 88%
“…The micrographs reveal two main microwear marks inside the scars: (a) scratches, along the direction of sliding; and (b) pits, randomly scattered within the scar, typically adjacent to scratches ( Figure 8A). 19,29,30 Sliding moves the microcontacts along, thus resulting in the observed scratches. Indeed, small-scale contacts at asperities are akin to microindentation events, where the concentrated stresses at the tip produce localized subsurface plastic deformation and fracture (median and lateral cracks).…”
Section: Methodsmentioning
confidence: 99%
“…Indeed, small-scale contacts at asperities are akin to microindentation events, where the concentrated stresses at the tip produce localized subsurface plastic deformation and fracture (median and lateral cracks). 19,29,30 Sliding moves the microcontacts along, thus resulting in the observed scratches. Subsurface microcracks may propagate toward the surface, where they become visible ( Figure 8B).…”
Section: Methodsmentioning
confidence: 99%